Pathogenic copy number variants in patients with congenital hypopituitarism associated with complex phenotypes. (10th January 2018) - Correa, Fernanda A.; Jorge, Alexander AL; Nakaguma, Marilena; Canton, Ana PM; Costa, Silvia S; Funari, Mariana F; Lerario, Antonio M; Franca, Marcela M; Carvalho, Luciani R; Krepischi, Ana CV; Arnhold, Ivo JP; Rosenberg, Carla; et al.
Summary: Objectives: The aetiology of congenital hypopituitarism (CH) is unknown in most patients. Rare copy number variants (CNVs) have been implicated as the cause of genetic syndromes with previously unknown aetiology. Our aim was to study the presence of CNVs and their pathogenicity in patients with idiopathic CH associated with complex phenotypes. Design and Patients: We selected 39 patients with syndromic CH for array‐based comparative genomic hybridization (aCGH). Patients with pathogenic CNVs were also evaluated by whole exome sequencing. Results: Twenty rare CNVs were detected in 19 patients. Among the identified rare CNVs, six were classified as benign, eleven as variants of uncertain clinical significance (VUS) and four as pathogenic. The three patients with pathogenic CNVs had combined pituitary hormone deficiencies, and the associated complex phenotypes were intellectual disabilities: trichorhinophalangeal type I syndrome (TRPS1) and developmental delay/intellectual disability with cardiac malformation, respectively. Patient one has a de novo 1.6‐Mb deletion located at chromosome 3q13.31q13.32, which overlaps with the region of the 3q13.31 deletion syndrome. Patient two has a 10.5‐Mb de novo deletion at 8q23.1q24.11, encompassing the TRPS1 gene; his phenotype is compatible with TRPS1. Patient three carries a chromosome translocation t(2p24.3;4q35.1) resulting in two terminal alterations: a 2p25.3p24.3 duplication of 14.7 Mb and a 4‐Mb deletion at 4q35.1q35.2. Conclusions: Copy number variants explained the phenotype in 8% of patients with hypopituitarism and additional complex phenotypes. This suggests that chromosomal alterations are an important contributor to syndromic hypopituitarism.